Haematology and histopathology of Nile tilapia parasitised by Epistylis sp., an emerging pathogen in South America - Valladão, G. M.R. [UNESP]; Levy-Pereira, N. [UNESP]; Viadanna, P. H.O. [UNESP]; Gallani, S. U. [UNESP]; Farias, T. H.V. [UNESP]; Pilarski, F. [UNESP] (My University, 2015)
Twenty Nile tilapia (Oreochromis niloticus) parasitised by Epistylis sp. were collected for haematological and histopathological analysis. Fish with >400 zooids showed increase in lymphocyte and decrease in neutrophil population (p<0.05), compared to the less parasitised group (<400). Histopathologic analysis showed that Epistylis sp. induces a chronic inflammatory response in the host, possibly provoked by constant contact with the fish skin.